Strategies to Control Illegal Fishing in the Waters of Pasir Limau Kapas District, Rokan Hilir Regency - Willy Irawan; Ridwan Manda Putra; Muhammad Fauzi (Jurnal Perikanan dan Kelautan, 2024)
The magnitude of the potential has led to the emergence of illegal fishing activities that cause losses to the state and surrounding communities. One of the water zones in Indonesia that has potential and is prone to illegal fishing is the Malacca Strait, including the waters of Rokan Hilir Regency. The research aims to formulate illegal fishing control strategies to prevent and stop illegal fishing activities. This research was conducted in Pasir Limau Kapas District, Rokan Hilir Regency, which consists of Panipahan Kepenghuluan, Panipahan Laut Kepenghuluan, and Panipahan Darat Kepenghuluan from March to July 2023. The primary data are obtained directly through observation and interviews, and secondary data is obtained from relevant agencies and institutions. Data analysis uses a quantitative approach to formulating illegal fishing control strategies using SWOT and descriptive analysis methods. The SWOT analysis results of controlling illegal fishing activities is a W-O (Weakness - Opportunities) strategy by considering existing opportunities and minimizing internal problems that become weaknesses. Some strategies that can be formulated include increasing surveillance in Pasir Limau Kapas Waters, increasing socialization of the impacts of illegal fishing and maintaining marine ecosystems, and improving fisheries support facilities in Pasir Limau Kapas District.